2018
DOI: 10.3389/fphar.2018.00687
|View full text |Cite
|
Sign up to set email alerts
|

The IGF2/IGF1R/Nanog Signaling Pathway Regulates the Proliferation of Acute Myeloid Leukemia Stem Cells

Abstract: Acute myeloid leukemia is an aggressive disease characterized by clonal proliferation and differentiation into immature hematopoietic cells of dysfunctional myeloid precursors. Accumulating evidence shows that CD34+CD38- leukemia stem cells (LSCs) are responsible for drug resistance, metastasis, and relapse of leukemia. In this study, we found that Nanog, a transcription factor in stem cells, is significantly overexpressed in CD34+ populations from patients with acute myeloid leukemia and in LSCs from leukemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 56 publications
(99 reference statements)
0
13
0
2
Order By: Relevance
“…IGF‐1 attracted our attention, as both IGF‐1 and IGF‐2 activate IGFR1. It has been reported that IGFR1‐mediated expression of Nanog promotes the formation of cancer stem cells of HCC and the proliferation of acute myeloid leukemia stem cells, linking to cancer invasion, metastasis, and drug resistance. Tenascin C encoded by TNC regulates cancer stemness by activate Notch signaling of cancer cells .…”
Section: Discussionmentioning
confidence: 99%
“…IGF‐1 attracted our attention, as both IGF‐1 and IGF‐2 activate IGFR1. It has been reported that IGFR1‐mediated expression of Nanog promotes the formation of cancer stem cells of HCC and the proliferation of acute myeloid leukemia stem cells, linking to cancer invasion, metastasis, and drug resistance. Tenascin C encoded by TNC regulates cancer stemness by activate Notch signaling of cancer cells .…”
Section: Discussionmentioning
confidence: 99%
“…Picropodophyllin (PPP; AXL1717) is a clinically utilized, selective, small molecule inhibitor of IGF-IR [2933]. It has been shown to be effective in inhibiting various types of cancers including those of the gastrointestinal tract, nasopharynx, liver, lung, ovary, soft tissues, and hematopoietic system including NPM-ALK + T cell lymphoma [21, 3446]. Recently, however, higher doses of PPP have been shown to induce bone marrow toxicity in some patients [30].…”
Section: Introductionmentioning
confidence: 99%
“…Primary human AML cells express insulin and IGF receptors, 23 and a recent article described associations between pretreatment serum levels of various IGF binding proteins and between the serum fraction of bound IGF and a favorable prognosis with increased survival. 24 Systemic insulin/IGF levels thus seem important for the effect of insulin/IGF1 in the AML cell microenvironment, and experimental studies further suggest that both insulin 25,26 and IGF 27 have growth-enhancing and/or antiapoptotic effects in primary human AML cells. However, the heterogeneity of constitutive and insulin-induced PI3K-Akt-mTOR network phosphorylation in primary AML cells has not been addressed previously, and our present study shows that constitutive phosphorylation (at least partly IGF dependent) differs between patients, but exposure to insulin adds further heterogeneity.…”
Section: Discussionmentioning
confidence: 98%